An Analysis of Phrasal Verbs in Subtitles of Sherlock – A Study in Pink - Sutrisno Sadji Evenddy; Welliam Hamer; Dhafid Wahyu Utomo; Hayun Hamdalah (Journal of English Education Studies, 2020)
The objective of this research is to describe the types and semantic distinctions of phrasal verb found in subtitles of TV-Series: Sherlock – A Study in Pink. The researchers used content analysis as research method and coding to collect data. The data sources of this research are phrasal verbs in subtitles of TV-Series: Sherlock A Study in Pink. This research used 3 steps in analyzing the data; data condensation, data display, drawing and verifying conclusions. Further, the researcher used investigator triangulation to verify and validate the data. As a result, there are 3 types of phrasal verbs found :intransitive, transitive-separable, and transitive-inseparable phrasal verbs. There are 30 data classified into intransitive phrasal verb, 23 data classified into transitive-separable phrasal verbs, and 5 data classified into transitive-inseparable phrasal verbs. The last, based on the analysis of semantic distinctions of phrasal verbs, it is found that there are 3 semantic distinctions of phrasal verbs, those are free idiomatic, semi idiomatic, and highly idiomatic phrasal verbs. There are 13 data classified into free idiomatic phrasal verbs, 22 data classified into semi idiomatic phrasal verbs, and 23 data classified into highly idiomatic phrasal verbs.